3 Years Expeimental Study on Abdominal Aortic Aneurysm Patients Who were Treated with Endovascular Aneurysm Repair in Dr. Mohammad Hoesin General Hospital Palembang During 1st of January 2018 â€“ 31st of December 2020 - Muhammad Febriandi Djunaidi; Kemas Muhammad Dahlan; Fahmi Jaka Yusuf (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2021)
Background: Abdominal aortic aneurysm (AAA) is a focal dilatation of the aortic segment with an increase of 1.5 times the normal value or â‰¥3 cm. The risk increases in old age and requires alternative surgery such as EVAR. EVAR is more useful in AAA therapy than surgery with wide incisions. Methods: This research was descriptive in RSMH Palembang for 5 years in 1st of January 2018 - 31st of December 2020 with variables of patient clinical characteristics and patient CTA results. Results: The results showed that AAA was more common in men, aged 60-69 years with high school education, risk factors such as a history of CHF, hypertension, CAD, and smoking habits. Angiographic CT result showed proximal diameter > 2 cm, PAU, calcification, iliac aneurysm, and lowest renal artery on the left side. All AAA patients had inferior limb thrombus and angulation > 600. The average of aneurysm is 5.8 cm in diameter and 9.23 cm in length. The mean diameter of the right iliac artery differs from the mean diameter of the left iliac artery. Conclusion: The diameter of the right femoral artery also differs from the diameter of the left femoral artery. AAA patients mostly had no history of CKD, COPD, and DM. The patients were hospitalized for an average of 7 days, especially in the ICU for 2 days.